BRAF V600E-Positive Multisite Langerhans Cell Histiocytosis in a Preterm Neonate - Sara V. Bates; Ashwini Lakshmanan; Adam L. Green; Jefferson Terry; Gayane Badalian-Very; Barrett J. Rollins; Patricia Fleck; Muhammad Aslam; Barbara A. Degar (Thieme Medical Publishers, Inc., 2013)
Abstract Hemorrhagic pustules with a "blueberry muffin" appearance accompanied by respiratory failure in a neonate present a challenging differential diagnosis that includes infections and neoplasms. We present a case of multiorgan, multisite Langerhans cell histiocytosis (LCH), positive for the oncogenic BRAF V600E mutation, in a preterm neonate. Infants with LCH pose a diagnostic challenge due to their heterogeneous presentations. This case is unusual in that the newborn presented with severe multiorgan involvement. Due to the rare incidence, wide spectrum of clinical manifestations, and high mortality rate, clinicians must maintain a high index of suspicion for LCH.